2023
DOI: 10.1111/cns.14294
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological insight into preventive intervention in posttraumatic epilepsy based on regulating glutamate homeostasis

Abstract: Background Posttraumatic epilepsy (PTE) is one of the most critical complications of traumatic brain injury (TBI), significantly increasing TBI patients' neuropsychiatric symptoms and mortality. The abnormal accumulation of glutamate caused by TBI and its secondary excitotoxicity are essential reasons for neural network reorganization and functional neural plasticity changes, contributing to the occurrence and development of PTE. Restoring glutamate balance in the early stage of TBI is expected to play a neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…In this study, it was found that compared with the control group, the release of Glu in the medium- and high-dose groups showed a significant upwards trend. The release of a large amount of Glu can cause overexcitation of neurons and eventually cause damage [ 45 ]. Injury causes a large amount of Na + and Cl − to flow into the cells, causing neuronal swelling and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that compared with the control group, the release of Glu in the medium- and high-dose groups showed a significant upwards trend. The release of a large amount of Glu can cause overexcitation of neurons and eventually cause damage [ 45 ]. Injury causes a large amount of Na + and Cl − to flow into the cells, causing neuronal swelling and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, lactate released by astrocytes can shuttle to neurons. 61 , 62 TBI leads to neuronal and glial metabolism uncoupling, 63 which can elicit excitotoxicity. 61 , 64 Severe TBI patients also exhibit disturbances in cerebral aspartate metabolism.…”
Section: Bioenergetic Disturbance In Tbimentioning
confidence: 99%
“…However, excessive glutamate in the brain leads to neuronal injury or death, known as glutamate excitotoxicity, which is implicated in many acute and chronic brain diseases, including stroke, traumatic brain injury, seizures, neuropsychiatric disorders, and neurodegenerative diseases such as Alzheimer's disease (AD), amyotrophic lateral sclerosis (ALS) and Parkinson's disease (PD) [2][3][4][5]. Inhibition of the glutamatergic system has a neuroprotective effect when brain ischemia, traumatic brain injury, epilepsy, AD, ALS, and mental disease occur [6][7][8]. This phenomenon may be used to prevent and treat these brain diseases.…”
Section: Introductionmentioning
confidence: 99%